The effect of bone marrow‐derived mesenchymal stem cells on chemotherapy induced ovarian failure in albino rats. Issue 10 (25th July 2016) - Gabr, Hala; Rateb, Moshira Abdelhakiim; El Sissy, Maha Hamdi; Ahmed Seddiek, Hanan.; Ali Abdelhameed Gouda, Sarah
Abstract: Objectives: Chemotherapy targets rapidly dividing tissues in the body. It destroys the progenitor cells in gonads resulting in premature ovarian failure. Studies have suggested that bone marrow‐derived stem cells can generate oocytes in chemotherapy treated female rats after transplantation. The present study aimed to assess mechanism of homing, the action of injected BM‐MSCs on ovarian function after ovarian damage.Experimental design : Seventy two female albino rats were randomly allocated into Control and CTX group, The Experimental protocol was lasted for 12 weeks during which serum FSH and E2 were monitored twice at the end of the 2nd week (12 rats) and 8th week (6 rats). Stem cells identification and homing were evaluated by Flowcytometry and tagging of stem cells with iron oxide particles respectively. Also, histopathological examination was done to evaluate both degeneration (6 rats at 4th week) and regeneration (6 rats at 12th week) of ovarian tissue together with assessment of the levels of TNF‐α in ovarian homogenate and IGF‐I as a growth factor in ovarian tissue.Principal observations : Partial improvement of E2 and FSH levels as well as ovarian architecture. Elevation of ovarian TNF‐ α levels and of IGF‐I immunohistochemical expressions in ovarian tissues of BM‐MSCs injected rats were noticed following homing of BM‐ MSCs in the ovarian stroma in both control and chemotherapy groups.Conclusion : Injected BM‐ MSCs can home in the stroma of the injured ovaries. IGF‐I and TNF‐ α may have a role in the attraction of stem cells in vivo.